NEGOSIASI BUDAYA SULAWESI TENGGARA DI ARENA GELANGGANG BUDAYA NEGERI SEMBILAN-MALAYSIA (The Cultural Negotiations of Southeast Sulawesi in the Arena of Gelanggang Budaya Negeri Sembilan-Malaysia) - Syaifuddin, NFN; Riana, Derri Ris; Rahmawati, NFN (Kandai, 2023)
The presence of the Southeast Sulawesi arts team at the Negeri Sembilan Cultural Center event in Malaysia in 2017 is interesting to study from the perspective of cultural negotiations. Processed and displayed art has a vital role in building cultural diplomacy missions. This research was conducted to determine the condition of Indonesia-Malaysia diplomatic relations and describe the types of art chosen as a cultural negotiating tool discussed in a descriptive-qualitative approach. The results of this study indicate that there are ups and downs in diplomatic relations between Indonesia and Malaysia. Apart from being caused by geocultural proximity, the same cultural roots sometimes become a potential source of conflict. The Southeast Sulawesi arts team succeeded in playing its role in cultural negotiations by choosing works and works of art, namely traditional and modern music; fine arts from two artists; poetry anthology of poets of two countries; monologue theatrical stage; and Southeast Sulawesi literature and culture magazine. Apart from that, the art team also took part in cultural dialogues and visits to the village library, where the event took place. The greeting and appreciation from Raja Luak Johol and the activity participants demonstrated the distinct achievement of the cultural mission of the activity, which involved three countries: Malaysia, Indonesia, and Singapore. Negeri Sembilan Cultural Center contributes to cultural diplomacy that provides space for equality, humanity, and peace. The relationship between the art network between Malaysia and Indonesia is getting closer. Kehadiran tim kesenian Sulawesi Tenggara pada ajang Gelanggang Budaya Negeri Sembilan di Malaysia pada tahun 2017 menarik untuk dikaji dalam perspektif negosiasi budaya. Kesenian yang diolah dan ditampilkan memiliki peran penting dalam membangun misi diplomasi kebudayaan. Itulah sebabnya, penelitian ini dilakukan untuk mengetahui kondisi hubungan diplomatik Indonesia-Malaysia dan membentangkan jenis kesenian yang dipilih sebagai alat negosiasi budaya yang dibahas dalam pendekatan deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa ada pasang surut dalam hubungan diplomatik antara Indonesia dan Malaysia. Selain disebabkan oleh kedekatan geobudaya, juga akar kebudayaan yang sama sehingga kadang menjadi sumber potensi konflik. Tim kesenian Sulawesi Tenggara berhasil memainkan perannnya dalam negosiasi budaya dengan memilih kerja dan karya seni, yakni musik tradisi dan modern; seni rupa dari dua perupa; antologi puisi penyair dua negara; pentas teater monolog; dan majalah sastra dan budaya Sulawesi Tenggara. Selain itu, tim kesenian juga mengikuti dialog budaya dan kunjungan ke perpustakaan desa, tempat pelaksanaan acara berlangsung. Sambutan dan apresiasi dari Raja Luak Johol dan peserta kegiatan menunjukkan pencapaian tersendiri misi kebudayaan pada kegiatan yang melibatkan tiga negara tersebut, yakni Malaysia, Indonesia, dan Singapura. Gelanggang Budaya Negeri Sembilan memberikan kontribusinya bagi diplomasi budaya yang memberi ruang bagi kesetaraan, kemanusiaan, dan perdamaian. Hubungan jejaring kesenian antara Malaysia dan Indonesia semakin erat terjalin.